On the zeros and critical points of a rational map - Xavier Buff (International Journal of Mathematics and Mathematical Sciences)
Let f:ℙ1→ℙ1 be a rational map of degree d. It is well known that f has d zeros and 2d−2 critical points counted with multiplicities. In this note, we explain how those zeros and those critical points are related.